Diseño de sitio web para la difusión y comunicación institucional de la unidad educativa Joaquín Lalama de la ciudad de Ambato provincia de Tungurahua.” - Aillón Solis, Christian Alejandro (2024)
The project focuses on developing a website for the "Joaquín Lalama" Educational Unit in Ambato, with the aim of improving institutional communication and online presence. The goal is to create an up-to-date digital platform that effectively disseminates academic activities, institutional achievements, and facilitates interaction with the educational community, representatives, and the general public. It is expected that this centralized website will improve both internal and external communication, strengthen the institution's image, and promote participation from all members of the educational community. With a solid online presence, the "Joaquín Lalama" Educational Unit is expected to achieve greater visibility at the provincial and national levels, contributing to more efficient management and a more committed educational community in the long term. This project aims to transform the way the institution communicates and interacts with its environment, leveraging digital tools to enhance its impact and reach within the educational community.